Modeling and Estimation of Nickel Laterite Resources Using Geocomputing Methods at North Konawa, Southeast Sulawesi - Langkoke, Rohaya (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Administratively, the research area is located in the Waturambaha area, North Konawe, Southeast Sulawesi province. The method used in determining the distribution and estimation of Ni laterite measurable resources is one of the geocomputational methods, Inverse Distance Wieght (IDW). From the interpolation of 82 drill points, it was concluded that the distribution of Ni levels is quite high (COG ≥ 1.2%) discriminated dominantly in the central to northern part and some points in the northwest of the study area, while low-grade Ni (
Keywords: Measurable Resources; Geocomputation; Modeling; IDW; Ore; Waste